Catatan Pemanfaatan Schizophyllum commune di Kampung Udapi Hilir, Papua Barat - Agessty Ika Nurlita; Ivan Permana Putra; Mahtub Ikhsan (UIN Sunan Kalijaga Yogyakarta, 2021)
Fungi are heterotrophic organisms that usually live as a saprophyte, parasites, or mycorrhiza. One of the macroscopic fungi that have the potential to be utilized by the community is the Schizophyllum commune. S. commune is known to be one of the edible wild mushrooms consumed in various parts of the world, including Indonesia. This fungus has been reported several times in Indonesia, but there are no records of this mushroom in West Papua and its use by local communities. Most of the publications about this mushroom in Indonesia are often without a description so that it becomes less popular among some Indonesians. This research aims to provide information on the existence of S. commune in West Papua along with a macroscopic description, distribution in Indonesia, and potential uses. The method used in this research is the opportunistic sampling method. Since this date, this fungi has been reported 30 times at 17 different locations in Indonesia. This information adds to the data on the diversity of S. commune and the status of its use in Indonesia. Several regions in Indonesia have used S. commune as food and medicine. However, in other parts of Indonesia, some people did not know this potential.